Characterization of Prasugrel Degradation Profile by Several Oxidative Reagents using HPLC and LC-MS/MS Technique - Bhukya, Vijay Nayak; Beda, Durga Prasad (Asian Journal of Chemistry, 2023)
Prasugrel, a derivative of thienopyridine functions as a prodrug that exerts irreversible inhibition on platelet ADP receptors by specifically targeting the P2Y12 receptor. In pharmaceuticals, the stability of the product plays a crucial role in establishing the shelf life of product. The second common degradation pathway next to hydrolysis is the oxidation. In practice, the oxidative stress studies were carried out using hydrogen peroxide (H2O2), free radicals, oxygen purging, transition metals, singlet oxygen, Fenton reagent, etc. This study compares the oxidative degradation behaviour of prasugrel hydrochloride using different oxidative stressors and was analyzed by HPLC using a method that could separate degradation products individually and from the drug. The degradation products formed under different stress conditions were characterized using LC-TOF-MS/MS. Analysis of accelerated stability samples of prasugrel formulation revealed that the degradation products formed under azobisisobutyronitrile (AIBN) and H2O2 stress conditions were simulated with the stability data. This study on prasugrel showed that the degradation products formed with H2O2 were also observed under hydrolytic conditions. In the pharmaceutical industry, H2O2 is the only oxidative stressor (< 95%) used to study the oxidation degradation of the sample. The present work has demonstrated that AIBN serves as a valuable oxidative stressor for accurately assessing the oxidative stability of drug.